Creatine supplementation in sport and medicine - a review of recent reports - Jagodowski, Piotr; Gawlik, Łukasz; Szpyra, Justyna; Banaszek, Agnieszka (Quality in Sport, 2024)
Introduction and objective The role of creatine as a dietary supplement to enhance ergogenic performance in strength sports is well established and researched, both among professionals and amateurs. In this article, we will focus not only on analysing creatine supplementation as an agent used in sport, but also as a supplement that may find a medical application. Review methods A literature search of Google Scholar and PubMed medical databases from the last eight years (2016-2024) was performed. Articles were searched in English using the following keywords: Creatine, Supplementation, Sport, Athletes Abbreviated description of the state of knowledge The role of creatine in strength sports is firmly established. Recent reports present creatine as an agent with many other uses. Endurance sports, rehabilitation or injury prevention are just a few of the areas mentioned where creatine finds its use. In the medical sciences, it is of interest to fields such as neurology, psychiatry, cardiology, geriatrics or rheumatology. Although many misconceptions have grown up around creatine, one of the best confirming its safety may be the fact that there are reports of benefits for pregnant women and the foetus. Summary Research shows the extensive use of creatine in various sports and medical fields. The high safety profile and efficacy in resistance training has been confirmed and is now known to an increasing number of people, not only in competitive sport. New promising reports in many areas of medicine and sport are described in an increasing number of reports, with the need for further research, often using more widely available modern technologies.